Modeling of indoor airflow around thermal manikins by multiple-relaxation-time lattice Boltzmann method with LES approaches. (17th January 2020) - Cheng, Xiaojie; Su, Ruoyu; Shen, Xiong; Deng, Tingxuan; Zhang, Delun; Chang, Di; Zhang, Boyue; Qiu, Shanshan
Abstract: As an effective CFD approach, Multiple-Relaxation-Time Lattice Boltzmann Method (MRT-LBM) has gradually gained its popularity in the past 20 years. In this article, a case that simulated the airflow patterns surrounding the human bodies were studied using MRT-LBM. The governing equation was solved by the MRT-LBM in the simulation. In order to calculate the boundary layer around the complicated geometry, wall-adapting local eddy viscosity (WALE) model was applied for the turbulence model. The D3Q19 and D3Q7 models were applied for the discretization of momentum and energy equation, respectively. In order to analyze the grid independence, three lattice densities were compared in this study. The simulation results were compared with the finite volume method (FVM) as well as the experimental data. Results showed that MRT-LBM with grid resolution of 0.01 m would obtain accurate results of airflow surrounding the human bodies. FVM required 5–6 times computation time than the MRT-LBM. Thereby, the MRT-LBM method can have advantages in the indoor airflow simulation field especially when the indoor geometry is complicated.